Peningkatan Keterampilan Mengajar Guru SD/MI melalui Pelatihan Media Pembelajaran Edugames Berbasis Teknologi: Quizizz dan Baamboozle - Ilmatus Sa'diyah; Adelia Savitri; Salsa Febiola Gading Widjaya; Falih Wicaksono; Al Danny Rian Wibisono (Publikasi Pendidikan, 2021)
The Covid-19 pandemic has changed many things, included learning methods in schools. All learning activities switch to an online system. This change raised several teaching obstacles faced by SD/MI teachers in Indonesia. The obstacle faced was the lack of mastery of technology for teachers so that the learning media used was less attractive. Based on a survey conducted, as many as 79.2% of parents stated that teachers mostly provide explanations of material through videos in WhatsApp groups and 45.8% of teachers provide video links from Youtube. Boredom was experienced by students during learning. Therefore, the community service team collaborates with partner schools to organize educational media training activities. In this case, the edugames taught are Quizizz and Baamboozle. This activity was attended by nine teachers from MI Asshibyan Dampaan, Cerme District, Gresik Regency. Activities taken place in a hybrid (offline and online). Quizizz materials were conducted offline at school on the first day, while bamboozle materials were conducted online through Zoom Meetings on the second day. After the presentation of the material by the team, the teacher also practiced compiling his own learning media with team assistance and then applied it in their respective classes. After the training activities, participants were able to arrange practice questions using the Quizizz learning media. The bamboozle media has not been implemented because the class does not take place via Zoom Meeting. The team hopes that this learning media can be applied continuously in online and offline classes.